Intravascular clearance of disseminating Cryptococcus neoformans in the brain can be improved by enhancing neutrophil recruitment in mice. Issue 7 (8th June 2016) - Sun, Donglei; Zhang, Mingshun; Liu, Gongguan; Wu, Hui; Li, Chang; Zhou, Hong; Zhang, Xiquan; Shi, Meiqing
Abstract : Cryptococcus neoformans induces neutrophil recruitment to the lung through C5aR signaling and actin polymerization. However, this neutrophil recruitment mechanism is weak in the brain compared to the lung resulting in less efficient fungal killing. Enhancing neutrophil recruitment in the brain vasculature reduced fungal burden in the brain. Abstract : Extrapulmonary dissemination of Cryptococcus neoformans ( C. neoformans ) is one of the most critical steps in the development of meningoencephalitis. Here, we report that clearance of the disseminating C. neoformans occurs within the brain microvasculature. Interestingly, the efficiency of the intravascular clearance in the brain is reduced compared to that in the lung. Intravascular clearance is mainly mediated by neutrophils, and complement C5a receptor signaling is crucial for mediating neutrophil recruitment in the vasculature. C. neoformans stimulated actin polymerization of neutrophils is critically involved in their recruitment to the lung, which is associated with the unique vascular structure detected in the lung. The relatively lower efficiency of fungal clearance in the brain vasculature correlates with less efficient recruitment of neutrophils. Accordingly, intravascular clearance of C. neoformans in the brain could be remarkably improved by increasing the recruitment of neutrophils. We conclude that neutrophils have the ability to eliminate C. neoformans arrested in the vasculature. However, insufficient recruitment of neutrophils limited the optimal clearance of this microorganism in the brain. These results imply that a therapeutic strategy aimed at enhancing the accumulation of neutrophils could help prevent cryptococcal meningoencephalitis.